A new genus and species of freshwater mussel from the Pearl River Basin in Guangxi, China (Bivalvia, Unionidae, Gonideinae) - Dai, Yu-Ting; Chen, Zhong-Guang; Li, Fan; Huang, Xiao-Chen; Ouyang, Shan; Wu, Xiao-Ping (Zoosystematics and Evolution, 2025)
A new genus and species of freshwater mussels, Guiunio rarus Chen, Li, Dai & Wu, gen. et sp. nov. , is described from the Pearl River Basin in China based on comparative morphology and molecular phylogeny. The new taxon belongs to the tribe Gonideini and can be distinguished from other genera by a unique combination of characteristics: shell medium-sized, moderately thick, flat, long, sub-glossy, opaque; anterior small, rounded and short; posterior extremely expanded, wide and long, with an indistinct obtuse angle in the middle of posterior margin; papillae on flap margin highly degraded. The validity of it is further supported by the molecular phylogenetic analysis based on COI , 16S and 28S sequences.